PENGARUH MODEL PEMBELAJARAN KOOPERTIF TIPE SNOWBALL THROWING BERBASIS MEDIA PAPAN WAKTU TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA DI KELAS II UPT SD NEGRI 068004 MEDAN TUNTUNGAN - Betta Leli Cahaya Pardede; Patri Janson Silaban; Rumiris Lumban Gaol; Bogor Lumbanraja; Nova Florentina Ambarwati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the Snowball Throwing type cooperative learning model based on time board media on student learning outcomes in mathematics learning in class II UPT SD Nrgeri 068004 Medan Tuntungan in the 2024/2025 Academic Year. The research method used is an experimental method with a quantitative research type. To obtain the required data, a test instrument of 30 questions. The number of research samples was 31 students based on the purposive sample technique. To determine the initial abilities of students, the study conducted a Pre Test with an average score of 49.93 which was in the less category. The results of the Post Test have an increase from the results of the Pre Test given previously with an average student score reaching 73.54 in the good category. It can be said that the level of success of student learning outcomes has increased as evidenced by the results of the correlation coefficient test calculation obtained the results of r_count ≥ r_table with a result of 0,814 ≥ 0,344. Furthermore, the hypothesis test that compares the value of t_count ≥ t_table. The value of t_count = 7,546 while t_table = 1,696. Because t_count ≥ t_table (7,546 ≥ 1,696) then H_a is accepted and H_o is rejected. Through the t-test, it can be concluded that there is a significant positive influence between the Snowball Throwing type cooperative learning model based on time board media (X) on student learning outcomes (Y).